Genome mining for peptidases in heat-tolerant and mesophilic fungi and putative adaptations for thermostability - de Oliveira, Tássio Brito [UNESP]; Gostinčar, Cene; Gunde-Cimerman, Nina; Rodrigues, Andre [UNESP] (Springer Nature, 2018)
Background: Peptidases (EC 3.4) consist of a large group of hydrolytic enzymes that catalyze the hydrolysis of proteins accounting for approximately 65% of the total worldwide enzyme production. Peptidases from thermophilic fungi have adaptations to high temperature that makes them adequate for biotechnological application. In the present study, we profiled the genomes of heat-tolerant fungi and phylogenetically related mesophilic species for genes encoding for peptidases and their putative adaptations for thermostability. Results: We generated an extensive catalogue of these enzymes ranging from 241 to 820 peptidase genes in the genomes of 23 fungi. Thermophilic species presented the smallest number of peptidases encoding genes in relation to mesophilic species, and the peptidases families with a greater number of genes were the most affected. We observed differences in peptidases in thermophilic species in comparison to mesophilic counterparts, at (i) the genome level: a great reduction in the number of peptidases encoding genes that harbored a higher number of copies; (ii) in the primary protein structure: shifts in proportion of single or groups of amino acids; and (iii) in the three-dimensional structure: reduction in the number of internal cavities. Similar results were reported for extremely thermophilic proteins, but here we show for the first time that several changes also occurred on the moderate thermophilic enzymes of fungi. In regards to the amino acids composition, peptidases from thermophilic species in relation to the mesophilic ones, contained a larger proportion of Ala, Glu, Gly, Pro, Arg and Val residues and a lower number of Cys, His, Ile, Lys, Met, Asn, Gln, Ser, Thr and Trp residues(P<0.05). Moreover, we observed an increase in the proportion of hydrophobic and charged amino acids and a decrease in polar amino acids. Conclusions: Although thermophilic fungi present less genes encoding for peptidases, these have adaptations that could play a role in thermal resistance from genome to protein structure level.
Keywords: Enzyme; Evolution; Modeling; Protease; Thermophilic fungi; Thermotolerant fungi